A first methodology for wind energy resource assessment in urbanised areas in Portugal - Simões, Teresa (2010)
The onshore wind power capacity in Portugal has increased very rapidly in the last five years and this high rate of development is expected to continue up to 2013 although at a slower rate. By then almost all sustainable onshore resource assessment will be deployed. Nevertheless, the full exploitation of the wind resource in Portugal offers other possibilities, among them the installation of small wind turbines (SWT), namely micro-turbines for domestic use in urban and constructed environments. To contribute to the needs of developers, investors and the overall population’s expectations and needs into this newer type of renewable market, a new a new line of research related to the wind resource assessment in urban and constructed areas was initiated. The present work presents a first user-friendly method to assess the urban wind potential at low experimental and computational costs, compatible with the scale of investment of micro-generation. A case study, where an urban area is identified and treated as very complex topography, was characterized in terms of wind resource, being the preliminary results presented here.